(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article analyzes the relationship between sensory experience and language acquisition within the Montessori teaching method. The study explores the cognitive basis of learning a language through movement, sight, and hearing. Based on Maria Montessori’s principles, it demonstrates that a sensory-rich environment and experiential learning enhance perception, thinking, and speech development. The integration of visual, auditory, and kinesthetic learning styles is also discussed as an effective approach to foreign language teaching.